Pangkalan Gojek : Ruang Produk Kapitalisme Digital - Holy Rafika Dhona; Gigih Mahatattwo (Fakultas Ilmu Komunikasi UKWMS, 2021)
Gojek driver base is a new social space formed by the tension between the development of communication technology and Indonesian drivers' work practices. It also creates further implications, namely the new meaning of a different space and new working model. Unfortunately, the communication dynamic in this event has not received much attention from communication scholars in Indonesia. Using the ethnography of space, this study found three things. First, Gojek drivers ambivalently interpret their base as 'office', but they did not consider their actions at the base as a work activity. This mystifies Gojek free drivers as 'casual workers'. Second, the absence of bases in the representation of space in the Gojek application forces driver to producing these bases independently. The cellular navigation, which gave rise to egocentric cartographic readings, became Gojek's instrument to intervene in a concrete space by making the driver the anchor of the production of a new social space. Third, the drivers then live the base with the image of brotherhood between the members of the base. They even become workers who can regulate themselves, which is in line with the logic of efficiency by digital capitalism such as Gojek.